Proposals for Construction of Tourist Image in Botosani County - Maria-Simona Cuciureanu (CES Working Papers, 2013)
Article aims to highlight the main elements unique tourism potential in Botosani County and need to develop a tourist images of this area. Turistic potential of rural areas is huge, but it is harnessed and exploited, though authenticity can create atractavitate territory for tourists. Rural tourism is an opportunity for existing potential for raising living standards, but it should have three primary phases: identification, promotion and development. Thus the study proposes several priority axes craerea and rural tourism brand, with the priority items identified.
Keywords: L83; Y91; 330; tourism image; rural tourism; development potential recovery Romania